Síntese e caracterização de nanocompósitos de caulinita/Tio2 com potencial aplicação como fotocatalisadores heterogêneos - Melo, Ana Paula Polzin de (2019)
The present work used kaolinite as the base material for the preparation of nanocomposite materials. The kaolinite was used in the in natura form, heat treated at 700 ºC and chemically treated using phosphoric and sulfuric acids. The purpose of the various treatments was to modify its structure and make it a better support for TiO2. Polymer precursors were synthesized using TiO2 and the kaolinite and TiO2 samples were combined to form the nanocomposites. These nanomaterials were applied in the heterogeneous photocatalysis process to photodegradate the reactive red dye 195. The nanocomposites were characterized by X-ray diffractometry (XRD), UV-Vis to determine Band Gap, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Dispersive Energy Spectroscopy (EDS). The degradation of the dye was monitored by UV-Vis spectroscopy (542 nm). By the FTIR spectra of the samples it was possible to verify the characteristic bands of kaolinite in natura, and the appearance of vibrations characteristic of metakaolinite. XRD analysis revealed that it was possible to increase the crystallinity of kaolinite samples after treatment with titanium citrate, this may be due to the adhesion of the oxide to the kaolinite surface. By the EDS analysis it was possible to estimate the amount of Ti in the synthesized samples, and its value was between 6.32 and 11.61%. ICP analysis shows that the samples have 26 to 40% Ti. The GAP data range from 1.69 to 3.44 for the samples with and without Ti in its composition.